Modulation of Multiple Signaling Pathways of the Plant-Derived Natural Products in Cancer - Sun, Li-rui; Zhou, Wei; Zhang, Hong-mei; Guo, Qiu-shi; Yang, Wei; Li, Bing-jin; Sun, Zhi-hui; Gao, Shuo-hui; Cui, Ran-ji (Frontiers in Oncology, 2019)
Natural compounds are highly effective anticancer chemotherapeutic agents, and the targets of plant-derived anticancer agents have been widely reported. In this review, we focus on the main signaling pathways of apoptosis, proliferation, invasion and metastasis that are regulated by polyphenols, alkaloids, saponins and polysaccharides. Alkaloids primarily affect apoptosis-related pathways, while polysaccharides primarily target pathways related to proliferation, invasion and metastasis. Other compounds, such as flavonoids and saponins, affect all of these aspects. The association between compound structures and signaling pathways may play a critical role in drug discovery.